Adult primary cervical rhabdomyosarcomas: A Multicentric cross-national case series. Issue 1 (27th November 2019) - Ricciardi, Enzo; Plett, Helmut; Sangiorgio, Valentina; Paderno, Mariachiara; Landoni, Fabio; Aletti, Giovanni; Prader, Sonia; du Bois, Andreas; Harter, Philipp; Colombo, Nicoletta
Abstract : Objectives: Adult primary cervical rhabdomyosarcoma is a very rare disease and data regarding treatment are sparce. The goal of this study was to report on our experience with the management of this rare entity, along with an evaluation of the literature. Methods: We conducted a review of the medical records at four centers from January 1990 to December 2017. We reviewed clinical characteristics including age at diagnosis, BMI, medical history and tumor stage, as well as treatment in the primary and recurrent settings and follow-up data. We reclassified tumors according to the Intergroup Rhabdomyosarcoma Study (IRS) clinical group. Results: A total of 15 patients were included in the analysis. Median age at diagnosis was 35 years (range 17–55). Median tumor size at presentation was 5 cm (range 3–10). Eleven patients had the embryonal variant, including five showing the botryoid subtype. Four patients had a pleomorphic rhabdomyosarcoma. Eleven patients had disease classified as IRS Clinical Group I, while the remaining four fell into groups II or III. Fertility-sparing treatment was offered to five patients. Primary treatment types were: surgery alone in eight patients, surgery followed by adjuvant chemotherapy in six patients, and neoadjuvant chemotherapy in two patients. The main risk factors for relapse were: IRS clinical group greater than I, tumor size greater than 5 cm, lymph nodal involvement, and non-embryonal histology. At a median follow-up of 35 months (range 3–282), we observed a 5-year overall survival rate of 78.2% and a progression-free survival of 58.2%. No patient in the IRS I group died of the disease. Three out of four patients in the IRS II-III group died of the disease (survival range 5–16 months following treatment). Conclusion: Our data show that cervical rhabdomyosarcomas account for at least two prognostic groups, demonstrating the existence of low-risk and high-risk patterns. The best predictor of prognosis appearsd to be the IRS clinical group classification system. IRS Group I tumors had an overall good prognosis and rarely recurred; when they did recur they were mainly local, following conservative treatment.